What would satisfy us?: Taking stock of critical approaches to transitional justice - Sharp, Dustin N. (International journal of transitional justice, 2019)
In recent years, a distinct critical turn in transitional justice scholarship has emerged, seeking to question the naturalness and inevitability of mainstream transitional justice theory and practice and to envision a broader and more holistic project. While in many ways a positive development, this newfound critical enthusiasm risks producing an unwarranted sense of pessimism and failure. This points to the need to better manage expectations as to what ‘success’ looks like even as we try to reimagine what transitional justice could become. To these ends, I draw upon and propose revisions to Robert Cox’s famous distinction between problem-solving and critical theory. To better maintain balance and perspective, I argue for the adoption of an ‘integrated’ approach to transitional justice critique that does more to engage with the difficult tradeoffs, policy choices and contextual realities that would inevitably be associated with efforts to implement an alternative vision of transitional justice.